Investigating Student Churn Among Business Schools in Higher Education - Yalcin, Aybueke; Uner, M. Mithat; Karatepe, Osman M.; Aboramadan, Mohammed (Tuba-Turkish Acad Sciences, 2023)
The purpose of our paper is to examine what the reasons for student churn are and why students begin their educational careers in a school of business and then leave and register at another university. Following a qualitative methodology, semi-structured interviews were conducted with 31 students (11 females, 20 males; mean age: 21.12; range: 19 to 25 years) who had switched from one business school to another in Ankara, the capital city of T & uuml;rkiye, and QSR NVivo 12 for Windows was used to analyze the qualitative data. The findings reveal that the main reason of student churn is associated with obstacles regarding the use of English as the medium of instruction. This is followed by dissatisfaction with the school or the department. The reasons for students preferring another university are also related to having friends at the university chosen, proximity to home, referrals, and family members. The study provides important insights to university administrators pertaining to the reasons associated with student churn in higher education. When the results are examined by university type, it is seen that the dissatisfaction with the university or department was the primary reason for the students who left the state universities, while the foreign language problem was the reason for the students who left the foundation universities. Considering the findings of the study, the university administration should concentrate on how to improve students' foreign language skills, invest more in research and innovation, and increase social activities to improve communication among students.
Keywords: English as the Medium of Instruction; Private Universities; Relationship Marketing; Student Churn; In-Depth Interview